Negative Pressure Pyrolysis Induced Highly Accessible Single Sites Dispersed on 3D Graphene Frameworks for Enhanced Oxygen Reduction. Issue 46 (4th September 2020) - Zhou, Huang; Yang, Tong; Kou, Zongkui; Shen, Lei; Zhao, Yafei; Wang, Zhiyuan; Wang, Xiaoqian; Yang, Zhenkun; Du, Junyi; Xu, Jie; Chen, Min; Tian, Lin; et al.
Abstract: Herein, we report a negative pressure pyrolysis to access dense single metal sites (Co, Fe, Ni etc.) with high accessibility dispersed on three‐dimensional (3D) graphene frameworks (GFs), during which the differential pressure between inside and outside of metal–organic frameworks (MOFs) promotes the cleavage of the derived carbon layers and gradual expansion of mesopores. In situ transmission electron microscopy and Brunauer–Emmett–Teller tests reveal that the formed 3D GFs possess an enhanced mesoporosity and external surface area, which greatly favor the mass transport and utilization of metal sites. This contributes to an excellent oxygen reduction reaction (ORR) activity (half‐wave potential of 0.901 V vs. RHE). Theoretical calculations verify that selective carbon cleavage near Co centers can efficiently lower the overall ORR theoretical overpotential in comparison with intact atomic configuration. Abstract : We report negative pressure pyrolysis to access dense single metal sites (Co, Fe, Ni etc.) with high accessibility dispersed on 3D graphene frameworks (GFs). Differential pressure inside and outside of metal–organic frameworks promotes cleavage of the derived carbon layers and gradual expansion of mesopores. The 3D GFs possess an enhanced mesoporosity and external surface area, contributing to an excellent oxygen reduction reaction (ORR) activity.